Ato protein interactions in yeast plasma membrane revealed by fluorescence lifetime imaging (FLIM) - Strachotová, Dita; Holoubek, Aleš; Kučerová, Helena; Benda, Aleš; Humpolíčková, Jana; Váchová, Libuše; Palková, Zdena (Biochimica et biophysica acta, 2012)
Each of the three plasma membrane Ato proteins is involved in ammonium signalling and the development of yeast colonies. This suggests that although these proteins are homologous, they do not functionally substitute for each other, but may form a functional complex. Here, we present a detailed combined FRET, FLIM and photobleaching study, which enabled us to detect interactions between Ato proteins found in distinct compartments of yeast cells. We thus show that the proteins Ato1p and Ato2p interact and can form complexes when present in the plasma membrane. No interaction was detected between Ato1p and Ato3p or Ato2p and Ato3p. In addition, using specially prepared strains, we were able to detect an interaction between molecules of the same Ato protein, namely Ato1p-Ato1p and Ato3p-Ato3p, but not Ato2p-Ato2p.
Keywords: buněčná membrána; membránové transportní proteiny; signální transdukce; Membrane Proteins; Signal Transduction; Spectrometry, Fluorescence; zelené fluorescenční proteiny; Saccharomyces cerevisiae - proteiny; mapování interakce mezi proteiny; fluorescenční spektrometrie; Models, Biological; Green Fluorescent Proteins; Fluorescence Recovery After Photobleaching; Membrane Transport Proteins; Subcellular Fractions; Protein Interaction Mapping; Saccharomyces cerevisiae Proteins; rezonanční přenos fluorescenční energie; biologické modely; Saccharomyces cerevisiae; membránové proteiny; FRAP; Cell Membrane; Fluorescence Resonance Energy Transfer; subcelulární frakce; regulace genové exprese u hub; Gene Expression Regulation, Fungal